Providing Access to Information on a Small Budget. - Carla G. Heister (Issues in Science and Technology Librarianship)
Presents research which dealt with providing access to information on a small budget. Lack of information resources at the Yale School of Forestry and Environmental Studies; Efforts of the students of the university to seek for other organizations and government agencies for information resources; List of Web portals that would be helpful for searching important resources.